2021
DOI: 10.1186/s12891-021-03976-5
|View full text |Cite
|
Sign up to set email alerts
|

A compliance real-time monitoring system for the management of the brace usage in adolescent idiopathic scoliosis patients: a pilot study

Abstract: Background Patient compliance is essential to the effectiveness of brace treatment for adolescent idiopathic scoliosis (AIS) patients. Subjective measurements like questionnaires and inquiries proved to be arguably inaccurate. Although some scholars have applied temperature/force monitors to measuring patient compliance objectively, few studies to date could monitor patient compliance in real time. The objective of this study is to describe and evaluate a compliance real-time monitoring system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…Due to the widespread use of web and app-based devices in our daily activities, it seems feasible to integrate these devices into the daily monitoring of IS in adolescent populations. Some web and mobile applications have been used previously in detection of AIS and the assessment of adherence to the brace [25,26]. However, the assessment of the psychological and physical state of the patient, which could explain individual differences in adherence and provides important information for the safety and effectiveness of the treatment, has been never included in the daily monitoring of adolescents with IS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the widespread use of web and app-based devices in our daily activities, it seems feasible to integrate these devices into the daily monitoring of IS in adolescent populations. Some web and mobile applications have been used previously in detection of AIS and the assessment of adherence to the brace [25,26]. However, the assessment of the psychological and physical state of the patient, which could explain individual differences in adherence and provides important information for the safety and effectiveness of the treatment, has been never included in the daily monitoring of adolescents with IS.…”
Section: Discussionmentioning
confidence: 99%
“…For example, mobile applications have been used as screening tools for AIS to measure the Cobb's degrees of curvature, even more accurately than traditional hand-held scoliometers [25]. Another alternative to sensors has been a web-based system for assessing brace compliance, which was well accepted by the participants [26]. Some limitations of the literature on alternatives to sensors for IS assessment should be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Even their predecessor, sensor based spinal orthosis, run an experimental course till date and lack widespread acceptance despite their introduction more than 2 decades ago. 13 None of the clubfoot studies demonstrate effectiveness of patient interventions/changes in practice based on the research data. 7e9 In fact, a later follow up prognostic study on the same subjects who used sensor based braces in initial months demonstrated that in long term, adherence as reported by caretaker or measured by sensor did not figure out as a factor in clubfoot relapse.…”
Section: Sensor Brace Orthosis Clubfoot Abstractmentioning
confidence: 98%
“…Ten studies Open access (described in 13 papers) met the selection criteria, all of which focused on AIS (figure 1). [23][24][25][26][27][28][29][30][31][32][33][34][35] We included six clinical trials, 23 28-34 three cohort studies, [24][25][26][27] and one cross-sectional study. 35 The included studies analyzed relatively small sample sizes (mean (range) of analyzed sample sizes: 101 (28-237)).…”
Section: Overviewmentioning
confidence: 99%
“…23 25 26 Both studies found evidence that this intervention significantly improved outcomes. 23 25 26 Karol et al 23 conducted an RCT and found that adolescents who received brace compliance reports and whose providers similarly received these reports and offered compliance counseling wore their TSLO braces significantly longer than those who did not. Zhu et al 25 26 incorporated a mobile phone application for providers to offer real-time compliance monitoring and counseling.…”
Section: Interventions For Patients Undergoing Bracingmentioning
confidence: 99%